Literature Review: Respon Morfologi Daun Tumbuhan Terhadap Faktor Lingkungan - Hafsya Yelmi Adisti; Vauzia Vauzia (Symbiotic: Journal of Biological Education and Science, 2025)
Environmental factors are important in influencing plant growth and development. In adapting to environmental factors, plants will respond through physiology, morphology and anatomy. One of the fastest aspects in responding to changes in environmental factors is leaf morphology, because leaves are the most sensitive and responsive organ to environmental changes. This literature review was written with the aim of knowing the morphological response of leaves to environmental factors. The method used is literature review by reviewing 25 articles selected to obtain 5 national journals, 8 international journals, and 4 indexed journals so that there are 17 articles. Based on the identification of 17 scientific articles, it was found that plants change aspects of leaf morphology such as leaf size, leaf shape, leaf thickness, and leaf colour as a form of adaptation to environmental factors such as climatic factors such as sunlight intensity, humidity, rainfall, and temperature, drought, altitude, anthropogenic environmental factors, water factors and soil factors.